HISTOLOGICAL LESIONS OF SLAUGHTERED CALVE'S KIDNEYS IN MOSUL SLAUGHTER HOUSE - H. K. Ismail (Basrah Journal of Veterinary Research)
The objective of present study was to investigate the gross and histopathological findings of calves kidneys slaughtered in Mosul abattoir. Pathological examination were carried out on fifty calves' kidneys. The most common gross lesions were included 20% multifocal white spots, 16% enlarged pale kidneys20% congested enlarged kidneys , 10% small shrunken kidneys, 14% hyperemic hemorrhagic kidneys, 20% kidneys without any gross lesions. The common observation in the histopathological examination of the kidneys revealed slight to severe mononuclear infiltration were commonly observed, widening of the Bowman's space were common, nephrosis, glomerulonephritis, interstitial nephritis, acute tubular degeneration and necrosis. Cysts were observed also in this study.